Contribution of the Agricultural Sector in the Economic Development in Nepal - Tamang, Soichya; Dahal, Gangadhar (Nepalese Journal of Management, 2025)
This study examines the contribution of agricultural sector in the economic development of Nepal. Economic development is the dependent variable. The selected independent variables are agricultural sector contribution, agricultural sector to gross value added, agricultural employment, and agricultural productivity. The study is based on secondary data. The total number of observations for the study consists of 60 for the study period of 2010/11 to 2021/22. The data were collected from ministry of finance and economic survey of Nepal. The correlation coefficients and regression models are estimated to test the significance and importance of contribution of agricultural sector in the economic development of Nepal. The study showed a positive impact of agricultural sector contribution on economic development. It indicates that higher the agricultural sector contribution, higher would be the economic development. Similarly, the study showed a positive impact of agricultural sector to gross value added on economic development. It indicates that higher the agriculture sector to gross value added, higher would be the economic development. Likewise, the study showed a positive impact of agricultural employment on economic development. It indicates that increase in agricultural employment leads to increase in economic development. Further, the study also showed a positive impact of agricultural productivity on economic development. It indicates that increase in agricultural productivity leads to increase in economic development.